Minimally Invasive Percutaneous Nephrolithotomy with a Novel Vacuum-assisted Access Sheath for obstructive calculous pyonephrosis ：A Randomized Study - Lai, Dehui; Xu, Wei; Chen, Meiling; He, Yongzhong; Li, Xun; Sheng, Ming; Zeng, Xingrong (Urology Journal, 2020)
Purpose: To investigate the safety and efficacy of Minimally Invasive Percutaneous Nephrolithotomy (MPCNL) combined with Vacuum-assisted Access Sheath in the treatment of obstructive calculous pyonephrosis. Materials and Methods: Seventy-six patients with obstructive calculous pyonephrosis, who were planned to receive MPCNL, were randomly divided into two groups. Group A was treated with Amplatz sheath combined with Cyberwand double probe ultrasound lithotripsy, and group B was treated with Vacuum-assisted Access Sheath (VAAS, ClearPetra, Well lead Medical) combined with holmium laser lithotripsy. The primary outcome was the operation successful rate. Other perioperative, and postoperative data such as operation time, stone free rate and complications were compared between groups. Results: Single 20F access sheath was established in all cases. All patients underwent one-stage procedure. Compared with group A, group B had a higher initial stone-free rate (84.2% vs 63.1%, P= .037). The operation time of group B was 56.3 ± 19.83 min, significantly shorter than that of group A at 70.4 ± 14.83 min. The complication rate of B group was 15.8%, which was lower than that of group A (P= .035 ). Five patients (15.8 %) of group B had a postoperative fever (>38.5 ºC) (Clavien grade 2) that required additional antibiotics; whereas 8 patients (21.1 %) of group A (P= .361). There was no blood transfusion in group A, and one case in group B required transfusion. Conclusion: One-stage MPCNL combined with Vacuum-assisted Access Sheath and holmium laser lithotripsy is a simple, safe, effective, and ergonomically practical method for selected patients with obstructive calculous pyonephrosis.